Open Access Challenges from a Sudanese researcher's perspective - Baleela, Rania (My University, 2019)
This is a presentation I was invited to give at SPARC Africa Open Access Symposium 2019. This presentation focused on challenges facing researchers accessing quality publications to help solve local problems. It also kind of relate achieving SDG targets by addressing local needs.
Supplemental Materials: https://osf.io/6cn94/
Keywords: Deathstalker; Manaseer; OASymp2019; Open Access; polyvalent antivenom; Scorpion; SDGs; Sudan